(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article examines the treatment of periodontitis, the importance of professional hygiene and the necessary medications, as well as methods for eliminating pathogenic flora in periodontal pockets and reducing inflammation.